Hysteresis versus PSM of ideal memristors, memcapacitors, and meminductors. Issue 20 (14th September 2016) - Biolek, Z.; Biolek, D.; Biolkova, V.
Abstract : The classical fingerprint of the ideal memristor with differentiable constitutive relation has recently been extended with a piece of knowledge that the area of the pinched hysteresis loop of a memristor driven by sinusoidal signal with fixed amplitude and increasing frequency disappears with an integer power of the frequency. This fingerprint is extended to the memcapacitor and meminductor, and it is also shown that the way the hysteresis disappears can be determined directly from the behaviour of the parameter versus state map (PSM) of the element in the neighbourhood of the initial operating point.